Social participation and depression among resettled Syrian refugees: examining a moderated mediation of social support and bonding or bridging social capital - Johnson-Singh, Charisse M.; Sengoelge, Mathilde; Engström, Karin; Saboonchi, Fredrik (Frontiers in Psychology, 2024)
Introduction Aspects of social capital, including social participation and social support, are among the factors influencing refugee mental health after resettlement. However, the mechanisms by which these aspects interact with one another and affect mental health remain unclear. This study investigates whether social participation influences depressive symptoms via social support and whether this influence is more prominent for Syrian refugees participating primarily in coethnic (bonding) networks compared to cross-ethnic (bridging) networks during the early stages of resettlement. Methods Using data from a cohort of 464 Syrian refugees recently resettled in Sweden, a moderated mediation analysis was conducted with multigroup structural equation modelling to investigate the mediatory role of social support in the association between social participation and depressive symptoms as well as the moderating role of bonding networks (social participation with other Syrians) versus bridging networks (social participation with Swedes) in this relationship. Results Frequent social participation, compared to rare or no participation, was significantly associated with lower depressive symptoms, regardless of whether participation included a broad or limited range of activities. Social support only mediated this relationship for those with primarily bonding networks, indicating that the mediation itself was moderated by network type. While participating in both bridging and bonding networks was associated with lower depressive symptoms, bonding networks amplified the effect of social participation on depressive symptoms via increased social support, resulting in an overall twofold decrease in depressive symptoms compared to those with bridging networks. Discussion These findings indicate that the frequency of social participation may be a more important consideration for fostering mental well-being in recently resettled refugees than the specific types of activities. Furthermore, while both bonding and bridging social networks confer mental health benefits, access to coethnic networks in early resettlement appears to provide a particularly crucial source of social support.